Political Clientelism—Beyond the Public Choice Explanation - Taj, Aamer; Abdullah, Fahad; Khan, Shahwali (The Journal of Humanities & Social Sciences, 2022)
This paper explores the theoretical perspectives and dynamics of voter-politician relationships, the determinants of voting behaviours and the parameters of electoral mechanisms in local governance with specific reference to the post-colonial societies in developing countries. The discussion begins with the distinguishing clientelism from other phenomena like corruption and pork barrel politics with specific reference to local governance. The impact of patronage employment and socio-economic fragmentation on the outcomes of pork barrel politics is evaluated in order to assess the dynamics of voting patterns. In addition, the paper also includes a discourse based on arguments that run counter to the public choice explanation of clientelistic exchanges. The identification of these antithetical stances to public choice theory will reveal why various forms of clientelism in certain societies make the overnight paradigm shift to a new form of political organisation, extremely complex.